2021
DOI: 10.5114/cipp.2021.105260
|View full text |Cite
|
Sign up to set email alerts
|

Restoring and preserving capacity of self-affirmation for well-being in Indian adults with non-clinical depressive tendencies

Abstract: BackgroundAlthough self-affirmation has been reported to enhance well-being and other positive life outcomes in normal adults, little is known about its capacity to restore and preserve well-being in adults with depressive tendencies. The current study attempts to expound the restoring and preserving capacity of self-affirmation for well-being in Indian adults with non-clinical depressive tendencies.Participants and procedureThe study used a sequential research design. Eighty participants (22-27 years) with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
(135 reference statements)
1
2
0
Order By: Relevance
“…Several studies have reported the beneficial effects associated with the practice of self-affirmations. Consistent with our findings, prior research has shown the efficacy of self-affirmation interventions, specifically in increasing positive emotional states while mitigating negative ones (Pandey et al, 2021(Pandey et al, , 2023.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have reported the beneficial effects associated with the practice of self-affirmations. Consistent with our findings, prior research has shown the efficacy of self-affirmation interventions, specifically in increasing positive emotional states while mitigating negative ones (Pandey et al, 2021(Pandey et al, , 2023.…”
Section: Discussionsupporting
confidence: 92%
“…Self-affirmation is a basic motivator that promotes self-worth and psychological well-being ( Pandey et al, 2023 ). It involves striving for self-integrity by being reminded of one's own self-esteem and other self-resources ( Pandey et al, 2021 ). Consequently, self-affirmation entails the act of reflecting on cherished values or one's own positive attributes, resulting in adaptive cognitive and behavioral outcomes.…”
Section: Personality Growth Interventionsmentioning
confidence: 99%
“…For example, Moroń (2018) found positive correlations between satisfaction with life scores and a "positivity ratio", representing a ratio between positive and negative emotions. Furthermore, Pandey et al (2021) reported that self-affirmation helps to restore well-being and to enhance satisfaction with self in depressive patients. In general, the results suggest that greater self-satisfaction is associated with better mental health variables.…”
Section: Self-satisfactionmentioning
confidence: 99%